Case history in the therapeutic clinic: educational-methodical textbook - Сиволап, Віктор Денисович; Назаренко, Олена Валеріївна; Кисельов, Сергій Михайлович; Солов'юк, Олександр Олегович; Земляний, Ярослав Вадимович; Syvolap, V. D.; Kyselov, S. M.; Solov'yuk, O. O.; Nazarenko, O. V.; Zemlyaniy, J. V. (Zaporizhzhya State Medical University, 2017)
The need for this methodical recommendations due to new requirements on writing case history in a therapeutic clinic. Methodical recommendations correspond to the program of discipline "Internal medicine" for students in higher educational institutions III-IV accreditation. Specialties: 7.12010001 "Medicine" 7.12010002 "Pediatrics." The manual provided with the necessary guidelines and requirements on writing case history of internal medicine and proper mastering practical skills during supervision of patient. Algorithms of differential diagnosis, clinical diagnosis components and examples of it formulation will allow students to learn the subject "Internal medicine" and develop clinical thinking of the future doctor.
Keywords: Internal Medicine; Case History